The Meaning of Jesus' Identity and Mission in Mark 8:31-38: A Reflection for God's People - Marthin Steven Lumingkewas; Bobby Kurnia Putrawan; Susanti Embong Bulan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2021)
This article aims to find the meaning of Jesus' identity and mission in Mark 8:31-38 which is reflected in the lives of God's people today. The method used is through the reading of Mark's narrative theology. According to Mark, the kingdom of God is the only kingdom where peace and justice are abundantly available to all, because the identity and work of Jesus is the true Son of God, and not Caesar. Becoming a part of this kingdom requires imposing what is the identity and mission of Jesus into the readers of Mark's text. Thus, it is reflected and applied to God's people today. The results of this study show that the identity and mission of Jesus is the duty and responsibility of God's people as the son of man to dare to suffer, be rejected, and be killed, for doing the work of the Father, and be resurrected after death.